Makna Dibenarkan Oleh Iman Dan Perbuatan Menurut Yakobus 2:14-26 - Samuel Julianta Sinuraya (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
AbstractSince his fall into sin, man has suffered from moral depravity and self-image damage before God. God took the initiative to restore the relationship with humans through the redemptive work of Christ. Through Christ's redemption, mankind who was originally sinful was justified by God's grace. James wrote the teaching that man who is justified by God through faith, should have deeds according to their faith. This research is a qualitative research with a grammatical historical approach. The aim of this research is to find the meaning of being justified by faith and deeds according to James 2: 14-26 and to explain the implications for today's believers. For James, the true form of faith can be seen through works. This means that a person whose actions do not reflect Christ's righteousness is essentially dead. AbstrakSejak jatuh ke dalam dosa, manusia mengalami kerusakan moral dan citra diri di hadapan Allah. Allah berinisiatif memulihkan hubungan dengan manusia melalui karya penebusan Kristus. Melalui penebusan Kristus, manusia yang semula berdosa dibenarkan oleh anugerah Allah. Yakobus menuliskan ajaran bahwa manusia yang sudah dibenarkan Allah oleh iman seharusnya memiliki perbuatan yang sesuai dengan imannya. Penelitian ini merupakan penelitian kualitatif dengan pendekatan historikal gramatikal. Adapun tujuan dari penelitian ini adalah menemukan makna dibenarkan oleh iman dan perbuatan menurut Yakobus 2:14-26 dan memaparkan implikasinya kepada orang percaya pada masa kini. Bagi Yakobus, bentuk iman yang sejati dapat dilihat melalui perbuatan. Seseorang yang perbuatannya tidak mencerminkan kebenaran Kristus pada hakekatnya mati.